PERWALIAN TERHADAP PENGURUSAN HARTA ANAK DI BAWAH UMUR (STUDI PENETAPAN PENGADILAN AGAMA BINJAI) - Widya Widya; Tan Kamello; Rosnidar Sembiring; Utari Maharany Barus (USU LAW JOURNAL, 2016)
The authority of the judiciary to give guardianship of religion against the management of the property related to children under legal protection of the child's property is in absolute terms the judiciary has the authority to give religious rights of guardianship against the management of the property of minors upon petition of the closest family the child custody determination of a court through religion. The responsibility of a guardian appointed by the Court to oversee religious treasures children under in the guardian does not exercise its obligations properly is the responsibility of the child's property is under guardianship as well as losses incurred due to the fault or negligence. Consideration of law made by judges in the determination of the custody of property management related children under IE the judge has the right judges law give consideration in accordance with the regulations and the provisions of the legislation relating to such matters. As for the consideration of the Tribunal judges who favor legal purposes namely benefit in line with the objectives of Islamic law that is giving the benefit of the people, though in Islam has been to explain that the mother, father, or sibling is a trustee for the son or brother of the applicant who are still minors. Keyword : Guardianship, Children Treasure, Religion Court